ENTREPRENEURIAL DEVELOPMENT AMONG YORUBA WOMEN TEXTILE TRADERS AT BALOGUN MARKET- LAGOS STATE, NIGERIA (2014)
In spite of prevailing challenges, many Yoruba women entrepreneurs have become successful in the informal textile trading. Few empirical studies on Yoruba women textile traders who have attained this success had been carried out. This study, therefore, examined how Yoruba women at Balogun market known to be the largest market textile trading in south west Nigeria with a large proportion of female gender, and an international market that serves ECOWAS countries with high volume of trading activities developed as entrepreneurs in textile trading. The study was of descriptive research design guided by social action theory. Forty in-depth interviews (IDIs) and Eight Focus Group Discussions (FGDs) were purposively conducted with women operating lock-up shops. Eighteen key Informants Interviews (KIIs) (male traders-5, historians-2, women trading from stalls-6 and retired women textile traders-5) were interviewed and eight case studies were done with wholesale textile traders. Archival materials were used to complement the primary data. Data were collected on the women’s historical experiences involving the process of entrepreneurial development to understand when and how they started textile trading; motivating factors asking why textile trading; access to entrepreneurial resources; organization of the textile trade and challenges faced by women textile traders. The data were subjected to Content analysis and ethnographic summaries. Involvement of Yoruba women in the textile trades at Balogun market dated back to pre-independence period. Socialization into textile trade was diverse, such as, early child development training through ascribed status, apprenticeship training for a specified period through achieved status under the guidance of mentorship usually known as “Madam‘’. The head of association prescribes modes of entry and exit for admission into the trade. Extensive social networking was enhanced by benefactors and friends. The prestige attached to textile trading largely motivated women into the trade. Start-up capital came from personal savings, gratuities from previous employment, loans from spouses and inheritance. Access to credit was through an informal credit system such as esusu and ‘gifts’ from manufacturers, bank credit facilities without collaterals and plough back profits. Marketing and promotion strategies such as monetary gifts and informal social relations with customers; pooling of resources to lower overhead cost; record keeping and auditing to enhance their trade were major strategies used to boost trade. Exclusive trading rights in special materials, continuous innovation and imitation of textile materials by women textile traders enhance wealth accumulation and facilitated entrepreneurial development. Challenges faced by women included exorbitant shop prices and warehouses lacking necessary facilities, banning some of the textile materials by the government and the vagaries of the informal economy. Entrepreneurial development process among Yoruba women textile traders was enhanced by ascribed and achieved statuses, continuous ability to access entrepreneurial resources, ability to innovate and imitate textile materials, resources pooling and risk sharing through appropriate social networking that lower head costs.